Św. Hieronim jako naśladowca języka i stylu autorów starożytnych na podstawie listów 1-24 - Wojtczak-Szyszkowski, Jerzy (Vox Patrum, 2020)
St. Jerome is known as an outstanding expert on ancient literature and a follower of its excellent authors as well as the classical Latin language. The relatively low interest in his work among younger philologists and patrologists prompted the author of the article to show the values of Jerome’s language and style imitating outstanding Latin writers and poets, especially Cicero. Already by showing his education and reading on the example of his letters, the author of the article wants to stimulate the desire for more serious studies of his works not insignificant, and often outstanding, not only in terms of theology, but also literary. Cited examples of some elements of the Latin used by St. Jerome show that he is rightly recognized for his abilities and knowledge.